Comprehensive human health risk assessment of heavy metal contamination in urban soils: insights from selected metropolitan zones - Ayaz, Harris; Nawaz, Rab; Nasim, Iqra; Irshad, Muhammad Atif; Irfan, Ali; Khurshid, Iram; Okla, Mohammad K.; Wondmie, Gezahign Fentahun; Ahmed, Zulkifl; Bourhia, Mohammed (Frontiers in Environmental Science, 2023)
This study aims to assess the extent of heavy metal contamination in urban soils in sixteen selected cities of Pakistan, encompassing the elements cadmium (Cd), lead (Pb), cobalt (Co), zinc (Zn), chromium (Cr), nickel (Ni), manganese (Mn), iron (Fe), and copper (Cu). The data utilized for this study was collected from online literature during the period 2005 to 2019. This study investigated potential threats to human health through a comprehensive analysis, considering standards such as Enrichment Factors (EF), Geo-accumulation Indices (Igeo), and Human Health Risk Assessment (HHRA). Geo-accumulation Index results indicated varied risk intensities, with Cu, Pb, Co, Mn, and Fe exhibiting "no pollution" levels, while other elements show "moderate to extremely contaminated" values. EF analysis provided evidence of heavy metal presence, revealing a spectrum from "no pollution" to "moderate to extremely high pollution" for Cd, Zn, Cr, Ni, and Cu. The health risk assessment identified both carcinogenic and non-carcinogenic dangers for adults and children. These findings highlighted the substantial contribution of identified sources such as industrial processes, vehicular emissions, sewage sludge, urban flooding, and the production and use of metallic materials that have elevated heavy metal levels in the urban soils. This established the link between urban industrial zones, human health, and long-term economic sustainability. This study provides essential guidance for decision-makers to develop effective strategies for soil remediation, enhanced industrial practices, and regulatory measures to address heavy metal contamination in urban areas, ensuring the well-being and sustainable environmental quality management in cities.